AKUNTANSI KELEMBAGAAN EKONOMI SYARIAH DALAM PERSFEKTIF IWAN TRIYUWONO - Rahmaniar, Rahmaniar; Dahoir, Ahmad (AL-QARDH, 2017)
Islam as a religion has been placed as an option and at the same teachings that provide guidance in human life adherents. Islamic economic development in Indonesia is progressing very rapidly, characterized by the emergence of sharia based financial institution. Financial institutions in practice cannot be separated from the financial statements or called in the language of business is accounting. This study focused on mentation of Iwan Triyuwono about the concept of sharia accounting, as stated in this theory that sharia enterprise theory and synergy binary opposition. The formulation of the problem in this study are (1) how the concept mentation of Iwan Triyuwono about sharia accounting? (2) how the relevance mentation of Iwan Triyuwono about accounting institutional of Islamic economics? Therefore the purpose of this study were (3) to describe the concept mentation of Iwan Triyuwono about sharia accountting (4) to describe the relevance mentation of about acoounting institutional of Islamic economics.